Nigerian para rubber seed meal as an energy and protein source for rats fed soybean meal or peanut meal supplemented diets - Orok E J; Bowland J P
Proximate, amino acid and fatty acid analyses were conducted on a sample of para rubber (Hevea brasiliensis) seeds (RS) obtained from Nigeria. The nutritive value of RS meal (RSM) for weanling Sprague-Dawley rats was tested with soyabean meal (SBM)-or peanut meal (PNM)-supplemented diets fed at three protein levels (20, 16 and 12;), by including in the diets 7.4 to 12.4;meal prepared from either fresh or autoclaved decorticated RS. The feeding period was 4 wk,in the last week of which energy and nitrogen digestibilities were determined followed by carcass analyses for protein, fat and ash. Kernels represented 57.0;of undecorticated RS meal from decorticated RS contained 3.9;moisture, 6.50 kcal gross energy/g, 43.3;crude fat, 18.3;crude protein, 3.8;crude fiber, 3.1;ash and 27.5;nitrogen-free extract. Rate of gain, energy and nitrogen digestibilities and carcass composition of rats fed diets containing RSM were comparable to those on the respective diets without RSM. Average food intake of rats fed RSM supplemented diets was lower (p<0.01) than that of rats on the SBM-supplemented diet. This lower consumption of diets containing RSM was consistent with their higher DE and ME (kcal/g food). Autoclaving RS had no consistent effects on the various measurements.
Keywords: Chemical composition; Nigeria; Nutritive value; Rats diet; Rubber seed meal